Gambaran Pengetahuan Orang Tua Tentang Pendidikan Seks Pada Anak Usia Sekolah Dasar Berdasarkan Umur, Pendidikan dan Pekerjaan di SDN Margahayu Raya Blok G Kota Bandung - Ice Aan Solihah; Fasha Fadillah Fauziah (STIKes Karsa Husada Garut, 2015)
Early childhod sex education can provide children’s understanding of her condition, the opposite sex and avoid sexual violence. In 2012, there are 2.637 cases of violence , which 48 percent are sexual violence. Compared with the database of the National Commission fo Child Protection in 2010 there is an increase in the number of cases of sexual violence in 2,85%. The aim of this research to describe the knowledge of parents regarding sex education to their children in elementary school based on age, education and occupation. This research is descriptive. Using sampling stratified random sampling technique. The numbered of samples was 78 respondents. Retrieving data used questionnaire and data were processed by statistical program used distribution tables, frequency and percentage. The result showed the highest value of parents knowledge about sex education was “low” category in 60,3%, based on age the highest value of respondent knowledge was “low” category mostly in 20-35 years old, based on education the highest value of respondent knowledge was “low” category mostly in Senior High School education and based on occupation the highest value of respondent knowledge was “low” category mostly in housewife. Hope that the school can improve mutual cooperation with the parents to improve sex education to their children in elementary school through formal and informal guidence.